Antioxidační charakteristiky třešní z různých regionů v České republice [Antioxidation characteristics of sweet cherries from different regions in the Czech republic] - Aneta Bílková; Pavlína Knapová; Dáša Jiroušová (Vědecké Práce Ovocnářské, 2022)
Sweet cherries are a very good source of phenolic compounds in our diet, including health-valuable anthocyanins, which have anti-inflammatory, antiviral and anti-tumor effects. This study concerned the determination of chemical attributes of three cherry varieties: ‘Regina’, ‘Kordia’, and ‘Tamara’ from organic and integrated production in four regions in the Czech Republic. The total antioxidant activity of the varieties, the content of total polyphenols, and anthocyanins were compared. The highest antioxidant potential was found for the variety ‘Kordia’ from the organic planting in Ostroměř thanks to the high value of the total antioxidant activity 179.0 ± 14.3 μmol Trolox/100 g fresh fruit, the content of total polyphenols 138.6 ± 15.7 mg gallic acid equivalent/100 g fresh fruit, and the content of anthocyanins 54.4 ± 6.8 mg/100 g fresh fruit.